2006
DOI: 10.1016/j.im.2006.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Information systems outsourcing: A literature analysis

Abstract: Abstract:Outsourcing has become one of the strategies adopted by businesses to manage their IS. During the last few years, the use of outsourcing has resulted in an increase in the volume of literature devoted to it. We decided therefore to analyse the literature with the aim of identifying the main topics, the methodologies most often applied and the authors and countries that have contributed most to the area of IS Outsourcing. We also intended to offer suggestions on improving research in this field. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(124 citation statements)
references
References 172 publications
5
107
0
4
Order By: Relevance
“…In recent literature analyses of major IS conferences and journal papers (Gonzalez et al 2006;Wiener 2006;Dibbern et al 2004), it was found that researchers drew on a multitude of economic, strategic, and social theories to explain IS outsourcing decisions of which transaction cost theoretical and resource-oriented thinking were most often used and also yielded the most consistent results across the various research studies. Taking these approved theories, the objective of this research study is to explain whether and why companies outsource different application types in a SaaS-setting, or, to put it differently, whether and why they adopt SaaS as on-demand sourcing option for specific application types.…”
Section: The Adoption Of Saas From Three Theoretical Perspectivesmentioning
confidence: 99%
“…In recent literature analyses of major IS conferences and journal papers (Gonzalez et al 2006;Wiener 2006;Dibbern et al 2004), it was found that researchers drew on a multitude of economic, strategic, and social theories to explain IS outsourcing decisions of which transaction cost theoretical and resource-oriented thinking were most often used and also yielded the most consistent results across the various research studies. Taking these approved theories, the objective of this research study is to explain whether and why companies outsource different application types in a SaaS-setting, or, to put it differently, whether and why they adopt SaaS as on-demand sourcing option for specific application types.…”
Section: The Adoption Of Saas From Three Theoretical Perspectivesmentioning
confidence: 99%
“…While there has been a plethora of academic research done on topics such as critical success factors of out- fect of ITO on IS staff, and two of those were actually looking at contract employees within the company [19]. While some more articles have been published on the impact of outsourcing on the IT worker since 2006, research seems to be still limited on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting topics or categories were neither mutually exclusive nor collectively exhaustive; one paper may fall upon several thematic areas, and more topics actually emerged as progress was made in the reading. Previous studies (Gonzalez et al 2006) have adopted a similar reasoning when it comes to classifying papers by topics: not limiting or forcing categories because of pre-conceived ideas (such as using only keywords, for instance); allowing for the appearance of additional topics when more papers are examined; finishing when saturation takes place, that is, when no different topics arise Table 5 classifies papers by topics, bearing in mind that the influence which Facebook has as an instrument for academic improvement is a common topic in all of them, and that it does not appear in this table. Although many of the topics suggested appear mixed and even blurred in a large number of papers, those papers which more evidently deal with a specific theme have been counted both in Table 5.…”
Section: Topics Analyzedmentioning
confidence: 99%